Angiomatosis intraorbitaria - Olivero, Marcelo; Gavira, Marcelo; Cañas, Sebastián (Revista Argentina de Neurocirugía, 2021)
Introduction: Cavernous angiomas are common entities, within orbital tumors, the presence of 2 or more than two is uncommon within an orbit, extraconal topography is the mostcommun, when they are multiple, they can be part of brain angiomatosis at some point in their evolution, therefore the need for evolutionary controls. Case Description: Pte. woman, 30 years who debuts with right proptosis, retrocular pain, diplopia, normal visual acuity. Tac two right, intracontal, solid, well-defined, retroocular intraorbital lesions are displayed that contacts (the innermost) the optic nerve and causes an external rotation of the eyeball. MRI: lesions appear more diffuse and heterogeneous, with signs of hemosiderin. Results: Explanatory video of the case, and structured steps of the technique. Right lateral orbitomia, ciliary incision extending to the lateral portion of the orbit, osteotomy of the right orbital lateral rim was used, then with drill the resection of the lateral wall is advanced. Traction points on the tear gland, allowing rotation of the eyeball and tensioning periorbita. It opens periorbita, identifying external straight muscle and by its upper edge advances in the deep dissection, recognizing sheath of the optic nerve, locating the cavernous angiomas, dissecting them circumferentially and removing them. Reconstruction of the orbital wall and orbital rim, closure by planes with cosmetic criteria, there was no oculo-motor deficit. Conclusion: Surgical resection is the standard treatment goal. The lateral orbitotomia was a minimally invasive approach, safe to this pathology.